P0073 Clinical characteristics of prostate cancer at a tertiary care medical centre in southern India over 11 years: A retrospective analysis. (July 2015) - Singhal, U.; Chawla, A.K.; Thomas, J.; Hegde, P.
Abstract : Background: Prostate cancer is the second most common contributor to the number of new cases of cancer in India. To our knowledge, little information exists regarding disease characteristics at the time of diagnosis in the Indian population. The aim of this study was to report the clinicopathological features of prostate cancer in a hospital-based population from southern India. Methods: We did a retrospective analysis of the medical records of 299 consecutive patients who had been diagnosed with prostate cancer between January 2001, and December 2011, and collected relevant data. Findings: The mean age at diagnosis was 68.9 (SD 8.63) years. Most patients (253 [84.6%]) presented with lower urinary tract symptoms, 65 (21.7%) had bone pain, and only 11 (3.68%) patients were asymptomatic. A pre-operative serum of prostate-specific antigen (PSA) value was available for 233 (77.9%) patients. Of the patients with available information, 191 (82.0%) had PSA levels of more than 20 μg/ml, 25 (10.7%) had levels between 10 μg/ml and 20 μg/ml, and only 17 (7.3%) had a level of less than 10 μg/ml. 242 (80.1%) patients were diagnosed by true-cut prostate biopsy, while 57 (19.1%) of patients were diagnosed after transurethral resection of prostate (TURP). 123 (41.1%) patients had bone metastasis detected using radio nucleotide bone scan. Androgen deprivation therapy was the most common initial treatment offered (285 patients [95.3%]). 108 (36.1%) patients underwent additional palliative TURP. 13 (4.35%) patients did not receive any treatment and could not be followed up. Only one patient underwent curative radical prostatectomy. The mean duration of follow-up was 15.92 months. Interpretation: Most patients in this study presented with either locally advanced or metastatic disease that was not amenable to treatment to cure. Further multicentre studies are warranted to better assess the epidemiology and disease characteristics of prostate cancer in the Indian population.